Philosophical environments for reading in rural schools - Morales, Lola María; Pulido-Cortés, Oscar (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The article presents the results of the research project Critical reading and philosophy as an experience: gatherings and possibilities in rural schools, developed with second- and third-grade students and teachers from Rafael Uribe Institution of Technical Education, San Rafael rural school in Toca, Boyacá. The general objective was to create philosophical environments that promote reading experiences among the aforementioned students. This article is divided into five parts. The introduction presents the context in which the project emerges and develops. The theoretical issues approach three conceptual categories that have been defined as philosophical environments, reading, and experience. The methodological tools describe the qualitative nature of the project and the instruments used. The findings and thresholds which are organized into six sections: the relationship with reading, reading as a possibility of creation, environments and resources for reading, questioning as a triggering factor, meaningmaking,∂and from observation to reading. Lastly, the conclusions compare the results with other research.